DEVELOPMENT OF POWER TOOLS LEARNING MEDIA MASED E-BOOK BASIC WORK LESSONS AUTOMOTIVE ENGINEERING CLASS X SMK NEGERI 1 SIMPANGKATIS: PENGEMBANGAN MEDIA PEMBELAJARAN MATERI POWER TOOLS BERBASIS E-BOOK PELAJARAN PEKERJAAN DASAR TEKNIK OTOMOTIF KELAS X SMK NEGERI 1 SIMPANGKATIS - Muhammad wahyudin Wahyudin; Widodo; Suparmin (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2024)
ABSTRACT The development of E-module media based on E-book competence of Basic Work of Automotive Engineering on Power Tools material, for SMK Negeri 1 Simpangkatis. Faculty of Teaher Training and Education Universitas Sarjanawiyata Tamansiswa Yogyakarta 2022. This research aims to produce E-book-based Emodule products in Basic Automotive Engineering Basic Work lessons on Power Tools materials for students of class X SMK Negeri 1 Simpangkatis. In addition to knowing the feasibility of E-module based on E-book in business and Motorcycle Engineering in SMK Negeri 1 Simpangkatis. Using 4D models manely (Define) defining, (Design) design, (Devlopment) development, adn (Dessiminate) disseminatin. Data collection consists of observations, interviews, adn questionnaires. The research engages material experts, teachers and learners to obtain an E-book based E-module fasibilty assessment and response. The data analysis technique used is a descriptive analysis technique. The resuts of the study showed that E-module media based on E-book after going through the media expert feasibilty test obtained a score of 4,03 with a “decent” category. Expert feasibility test score 4,73 with “very decent” and test with PDTO teachers 4,55 with “very decent” categories and small-scale tests of 4,17 categorized as “worthy”. Last in the test with a wide scale score 3,88 with the category “decent”. Keywords: Media Development, E-book, Learning Power Tools